Development of assistive technology e-books basic concepts of art for children with learning disabilities - Lina Novita; Fitri Siti Sundari; Lungguh Halira Vonti; Ratih Purnamasari (Jurnal Pendidikan dan Pengajaran, 2022)
The general school curriculum has not fully provided the concept of learning for children with special needs such as for children with learning disabilities. E-books are teaching materials as assistive technology, specially designed for students with learning disabilities. The aims of this study developing teaching materials in the form of e-books as learning aids for children with learning disabilities. This study is carried out base on the needs and learning styles of students. The subjects in this study consisted of expert testing and limited product user testing, in this case students. The sample selection of the test subjects was carried out by purposive sampling. Therefore, the research and development (R&D) approach was used in this study. The model developed using ADDIE. The expert validation stage is carried out on curriculum experts, media, and education practitioners. The trial was carried out on students at various levels, (1, 3, 5, and 7) with a total of 25 respondents. The data collection technique used a questionnaire with a Likert scale. The results showed that the development of assistive technology for e-books with the basic concept of art received a good response, was understandable, looked attractive, and was effective or feasible to use. Students achieve a better level of socialization, successfully achieved most of the lesson plan program goals such as motor, speech, language, reading, writing and memory development.